The Porphinoids - Versatile Biological Catalyst Molecules - Bernhard Kräutler (CHIMIA)
The natural porphinoids, such as the iron complex heme, the magnesium complex chlorophyll a, the nickel complex coenzyme F430, and the (corrinoid) cobalt complex coenzyme B12 play central roles in all spheres of life, e.g. as cofactors for oxygen or electron transport, for collecting light and transforming energy, and as catalysts in biosynthesis. – How the porphinoid structures developed in nature, how their often unique properties arise from special interactions between the bound metal ions and the macrocyclic ligands, and to which particular chemical reactivities and modes of action the porphinoids owe their specific biological functions – these are central questions to this topic. The latter ones lead ahead to the prospect that such properties might not only be beneficial to the living nature, but could be exploited profitably otherwise, be it by the use of porphinoid compounds as catalysts for synthesis, for the storage and conversion of energy, or for medical treatment. – For these reasons special attention has been given to the porphinoid metal complexes not only from the natural sciences, particularly from (organic and inorganic) chemistry and biology, but recently these molecules attract interest also in the areas of medicine and energy technology.